1995
DOI: 10.1227/00006123-199505000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Balloon Occlusion for Dissecting Vertebral Aneurysms Accompanied by Subarachnoid Hemorrhage

Abstract: Five patients with spontaneous dissecting vertebral aneurysms presenting with subarachnoid hemorrhage were treated with endovascular proximal balloon occlusion after a successful balloon Matas' test. Occlusion was performed in the extracranial portion of the vertebral artery after the potentially dangerous period of cerebral vasospasm. Two patients rebled preoperatively during the waiting period. Although angiograms demonstrated residual aneurysmal dilatation for four of the five patients, postoperative hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…Endovascular treatment has largely replaced surgery as the treatment of choice for ruptured VA dissecting aneurysms [37][38][39][40][41][42][43][44]. Initially, proximal occlusion of the VA (parent vessel occlusion) with detachable balloons or coils was attempted [45,46]. However, these procedures are not always effective in preventing re-rupture, and some investigators have reported rebleeding after proximal occlusion [40,47].…”
Section: Endovascular Treatment Of Intracranial Vertebral Artery Dissmentioning
confidence: 99%
“…Endovascular treatment has largely replaced surgery as the treatment of choice for ruptured VA dissecting aneurysms [37][38][39][40][41][42][43][44]. Initially, proximal occlusion of the VA (parent vessel occlusion) with detachable balloons or coils was attempted [45,46]. However, these procedures are not always effective in preventing re-rupture, and some investigators have reported rebleeding after proximal occlusion [40,47].…”
Section: Endovascular Treatment Of Intracranial Vertebral Artery Dissmentioning
confidence: 99%
“…Whilst it is necessary to treat this condition in a timely fashion, the exact treatment option is open to debate. Endovascular PAO is one of the several treatment options, and in the small case series of Tsukahara et al (n=5), there was no re-bleeding during the follow-up period [28]. Similarly, Yamaura et al [11] used GDC coils for PAO in six patients, again with no re-bleeds during the follow-up period.…”
Section: Discussionmentioning
confidence: 97%
“…However, a proximal occlusion may not always prevent re-rupture since the flow from the contralateral vertebral artery or anastomotic vessels, e.g. costocervical, thyrocervical and occipital arteries, may persist [28]. In the case series of Rabinov et al, 14 patients underwent proximal occlusion and two of these patients suffered re-haemorrhage, one of which died and the other underwent a trapping procedure [5].…”
Section: Discussionmentioning
confidence: 99%
“…Proximal occlusion of the parent vertebral artery by endovascular techniques or clipping may be useful for the treatment of dissecting aneurysms [4, 710]. However, such treatment does not always completely prevent rerupture, because blood flow may persist from the contralateral vertebral artery [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, such treatment does not always completely prevent rerupture, because blood flow may persist from the contralateral vertebral artery [11]. Some instances of growth [10] or rebleeding [4, 12–15] after proximal occlusion of the parent artery have been reported. When the dissection site is located in the vertebral artery proximal to the PICA division, proximal occlusion may be effective [16], since retrograde blood flow from the contralateral vertebral artery will supply the PICA beyond this site.…”
Section: Discussionmentioning
confidence: 99%